PENERAPAN BLENDED LEARNING BERBASIS INKUIRI DALAM MEMBEKALKAN KETERAMPILAN KOLABORASI SISWA SMA PADA MATERI BIOTEKNOLOGI - Imelda Gita Fitria, - (2022)
This study aims to analyze the application of inquiry-based blended learning in providing high school students' collaboration skills on biotechnology material. The method used is a descriptive method. The research was conducted in Senior High School in Sukabumi City by using purposive sampling technique. Data was collected through an instrument in the form of an observation sheet. The research data were analyzed to get a description of the collaboration skills of students in class XII Mipa 1 and an overview of the collaboration skills of each group for each indicator, as well as to analyze the indicators of the best collaboration skills in that class. The average result of students' collaboration skills as a whole is 87% with a very high category. Furthermore, the indicators for the best collaboration skills indicators include 3 indicators, namely Collaborating with various types of people; Dividing tasks according to the ability of group members and Participating respectfully with the three percentages each of 90% are included in the very high category, while the lowest student collaboration skill indicator in XII Mipa 1 is Contributing to solving problems with 82% which categorized is very high. Keywords: Collaboration Skills, Blended Learning, Inquiry Model, Biotechnology